I ( r , n ) = ∫ − ∞ 0 x r e n x d x where r , n ∈ Z .
X = n = 1 ∑ ∞ r = 0 ∑ ∞ I ( r , n ) 1
Find ⌊ 1 0 4 X ⌋
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hi Raghav, can you suggest any method on identifying how to start solving these types of questions . It took me quite some time before I actually solved it .
Thanks for the same :)
Log in to reply
Hmm... Maybe we could start by expressing the given entity in terms of the parameters of the summation. That is, we usually begin by finding the general expression for the r t h term and then summing it.
Please justify the change in the order of summation signs. This is not an absolutely convergent sequence, so you cannot just interchange them.
Also, can you justify why d n d J r − 1 = J r ? Note that you are pushing the differential through the integral, hence that step requires slight justification.
Well, Raghav's solution is interesting but here is mine just for diversity.
I ( r , n ) = ∫ − ∞ 0 x r e n x d x = − ∫ 0 ∞ x r e n x d x
Substitute n x = − u ⇒ x = n − u ⇒ n − d u = d x
= − ∫ 0 ∞ n r ( − 1 ) r u r e − u n − d u
= n r + 1 ( − 1 ) r ∫ 0 ∞ u r e − u d u
= n r + 1 ( − 1 ) r ∗ Γ ( r + 1 )
I ( r . n ) 1 = n r ! ( − n ) r
n = 1 ∑ ∞ n r = 0 ∑ ∞ r ! ( − n ) r
Well, the sum is quite easy as we can see that the first sum is just equal to e − n . Then the final sum becomes -
n = 1 ∑ ∞ n e − n
This can be solved easily by considering this base sum - 1 + x + x 2 + . . . = 1 − x 1 (first differentiating this, then multiplying it by x and then substituting x = e .
Therefore, we get the final answer as -
( e − 1 ) 2 e
I ( r , n ) = ∫ − ∞ 0 x r e n x d x = ∫ ∞ 0 ( − n t ) r e − t ( − n 1 ) d t = n r + 1 ( − 1 ) r Γ ( r + 1 ) = n r + 1 ( − 1 ) r n ! Let − t = n x , x = − n t , d x = − n 1 d t Γ ( ⋅ ) is Gamma function
Therefore, we have:
X ( 1 − e 1 ) X ⟹ X = n = 1 ∑ ∞ r = 0 ∑ ∞ I ( r , n ) 1 = n = 1 ∑ ∞ r = 0 ∑ ∞ n ! ( − 1 ) r n r + 1 = n = 1 ∑ ∞ n r = 0 ∑ ∞ n ! ( − 1 ) r n r = n = 1 ∑ ∞ n e − n = n = 0 ∑ ∞ e n + 1 n + 1 = e 1 n = 0 ∑ ∞ e n n + e 1 n = 0 ∑ ∞ e n 1 = e X + e 1 ( 1 − e 1 1 ) = e 1 ( e − 1 e ) = ( e − 1 ) 2 e ≈ 0 . 9 2 0 6 7 3 5 9 4 Note that n = 1 ∑ ∞ n e − n = n = 0 ∑ ∞ e − n
⟹ ⌊ 1 0 4 X ⌋ = 9 2 0 6
gamma function ,
then taylor series if e,
then diff w.r.t x of sum e^(-x)
Problem Loading...
Note Loading...
Set Loading...
J 0 = ∫ − ∞ 0 x 0 e n x d x = n 1 d e f i n e J r = d n d J r − 1 d n d J 0 = J 1 = ∫ − ∞ 0 x e n x d x = n 2 − 1 d n d J 1 = J 2 = ∫ − ∞ 0 x 2 e n x d x = n 3 2
What we are doing here is differentiating the integral with respect to n . Since we are differentiating with respect to n , we can treat x as a constant. And hence it can be seen that the r t h derivative of J 0 will contain r t h power of x inside the integral.
⇒ d n d J r − 1 = J r = ∫ − ∞ 0 x r e n x d x = n r + 1 ( − 1 ) r r ! ⇒ J r = I ( r , n ) = n r + 1 ( − 1 ) r r ! ⇒ ( I ( r , n ) ) − 1 = r ! ( − 1 ) r n r + 1 ⇒ ∑ r = 0 ∞ ( I ( r , n ) ) − 1 = n e − n ⇒ ∑ n = 1 ∞ ∑ r = 0 ∞ ( I ( r , n ) ) − 1 = X = e 1 + e 2 2 + e 3 3 + e 4 4 + . . . X = e 1 + e 2 2 + e 3 3 + e 4 4 + . . . e X = e 2 1 + e 3 2 + e 4 3 + . . . ⇒ X ( 1 − e 1 ) = e 1 + e 2 1 + e 3 1 + e 4 1 + . . . = e − 1 1 ⇒ X = ( e − 1 ) 2 e = 0 . 9 2 0 6 7 ⇒ ⌊ 1 0 4 X ⌋ = 9 2 0 6